Recent advances in breeding for Striga resistant extraearly maize for the savannas of West and Central Africa - Badu-Apraku, Baffour; Menkir, A.; Lum, A.F.; Fakorede, M.A.B.; Ibikunle, O. (2007)
Striga hermonthica is a major constraint to increased maize production and productivity in the savannas of West and Central Africa OVCA. The IITA-WECAMAN Maize Program has developed two extra-early source populations and several extra-early varieties, synthetics and inbred lines with resistance/tolerance to drought and/or S. hermonthica, eleven extra-early maturing varieties were evaluated at Ferkessedougou, Abuia and Mokwa in 2002 and at Mokwa and Abuja in 2004 under artificial Striga infestation and Striga- free conditions. In another trial conducted at Mokwa and Abuja in 2004, 36 extra-early maturing inbred lines were evaluated under Striga infestation and Striga-free conditions. Significant differences occurred among the varieties for grain yield under both infested and Striga-free conditions. Several promising Striga resistant extra-early maturing varieties (2000Syn EE W, 99 Syn EE-W and Sine TZEE-W STil were identified based on grain yield, Striga damage ratings and Striga emergence counts. Cluster analysis of the extra-early inbred lines, based on the similarity of quantitative characters, produced four and six major clusters under Striga infested and Striga -free conditions, respectively. The extra-early inbred lines assigned to each cluster under Striga infestation were different from those of the corresponding clusters of the Striga-free conditions. Superior specific hybrid combinations could be obtained by crossing inbred lines of different clusters rather than matings within clusters and by selecting parents with high grain yield and low Striga damage symptoms. Several promising extra-early maturing inbred lines were identified as sources of Striga resistance for the development of synthetic varieties and population.